2021
DOI: 10.3390/healthcare9030296
|View full text |Cite
|
Sign up to set email alerts
|

Pricing and Reimbursement Pathways of New Orphan Drugs in South Korea: A Longitudinal Comparison

Abstract: This study aimed to analyze four current pathways affecting the listing and post-listing prices of new orphan drugs (ODs) in South Korea. These mechanisms were: (1) essential OD, (2) pharmacoeconomic evaluation (PE) waiver OD, (3) weighted average price OD, and (4) PE OD. We analyzed the ratio of the listing price of 48 new ODs to the average adjusted price (AAP) of seven advanced countries and examined the change in the post-listing price. Descriptive statistics were used to analyze the listing and post-listi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The governments pledged hundreds of millions of dollars to support the local digital health industry. The prediction of individual health insurance costs is an essential task in the healthcare system, particularly for people with orphan diseases [2][3][4]: prevention and medical insurance help to decrease the cost of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The governments pledged hundreds of millions of dollars to support the local digital health industry. The prediction of individual health insurance costs is an essential task in the healthcare system, particularly for people with orphan diseases [2][3][4]: prevention and medical insurance help to decrease the cost of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the Korean government has given leeway with a wide range of incremental cost-effectiveness ratio (ICER) thresholds [maximum 50 million/quality-adjusted life year (QALY)], particulars of RSA, and exemption rules for CEA and pharmacoeconomic (PE) waivers to improve patients' access to innovative new drugs (52)(53)(54)(55). For the cases of orphan drugs, anticancer drugs, and severe life-threatening diseases, the CEA can be exempted, and the expenditure-capped RSA becomes effective and the prices of A7 countries are referred to as reference prices (Table 4).…”
Section: Risk Sharing Agreementmentioning
confidence: 99%
“…Recently, the Korean government planned to enhance the application of MEAs in order to facilitate access to high priced medicines ( Ministry of Health and Welfare MOHW, 2017 ). This built on previous studies that had investigated the positive impact on patient care with increased access to new treatments, particularly those for cancer and orphan diseases ( Kim et al, 2017 ; Yoo et al, 2019 ; Kim et al, 2020 ; Lee, 2021 ). Yoo et al (2019) reported that the introduction of MEAs and cost-effectiveness analysis waiver track, alongside increasing patient’s co-payments where there were concerns with their cost-effectiveness, contributed to improving patient access to new treatments.…”
Section: Introductionmentioning
confidence: 99%